Phytoestrogens and women’s health: Implications for fibroids and breast cancer – a scoping review - Lesnik, Nell; Tenfelde, Sandy (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
ABSTRACTBackground: As both uterine fibroids and breast cancer are estrogen dependent tumors, it is crucial to understand how phytoestrogen intake affects the development and progression of these conditions. Most of the research in this area has focused on soy isoflavones, yet a plethora of other phytoestrogens exist.Objective: The aim of this scoping review was to examine the current literature to determine the relationship between phytoestrogen intake, and the development and progression of uterine fibroids and breast cancer.Methods: The Scopus database was searched to identify relevant articles published within the past five years.Results: A total of 5,590 articles were identified in the original search, and 22 articles were included in the final review, with a total of 218,752 female participants (>18 years) across all studies. The findings of this scoping review suggest that consuming phytoestrogen-rich foods, such as soy or flaxseeds, either has no effect on breast cancer risk, or that it may possibly decrease the risk of breast cancer Additionally, supplementation with 300-900 mg of epigallocatechin gallate (EGCG), a phytoestrogen found in green tea, shows promise as a complementary treatment for fibroids.Conclusion: Current evidence suggests that dietary phytoestrogen intake does not increase the risk of breast cancer. Additionally, EGCG may be a future complementary treatment for reducing fibroid size, although more research is needed to confirm this finding. Keywords: Breast cancer; EGCG; fibroids; phytoestrogens